The Construct and Predictive Validity of a Dynamic Assessment of Young Children Learning to Read: Implications for RTI Frameworks - Fuchs, Douglas (J Learn Disabil, 2011)
The purpose of this study was to examine the construct and predictive validity of a dynamic assessment (DA) of decoding learning. Students (N = 318) were assessed in the fall of first grade on an array of instruments that were given in hopes of forecasting responsiveness to reading instruction. These instruments included DA as well as one-point-in-time (static) measures of early alphabetic knowledge, rapid automatized naming (RAN), phonemic awareness, oral vocabulary, listening comprehension, attentive behavior, and hyperactive or impulsive behavior. An IQ test was administered in spring of second grade. Measures of reading outcomes administered in spring of first grade were accuracy and fluency of word identification skills and reading comprehension. Factor analysis using principal axis factor extraction indicated that DA loaded on a first factor that also included language abilities and IQ, which the authors refer to as the “language, IQ, and DA” factor. It was relatively distinct from two additional factors: (a) “speeded alphabetic knowledge and RAN” and (b) “task-oriented behavior.” A three-level (children nested within classroom; classrooms nested within school) random intercept model with fixed effects predictors suggested that DA differed from word attack in predicting future reading skill and that DA was a significant predictor of responsiveness to instruction, contributing unique variance to end-of-first-grade word identification and reading comprehension beyond that explained by other well-established predictors of reading development.